2022
DOI: 10.5187/jast.2022.e84
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory effects of dairy probiotic strains Bifidobacterium animalis ssp. lactis HY8002 and Lactobacillus plantarum HY7717

Abstract: Probiotic strains Bifidobacterium animalis ssp. lactis HY8002 and Lactobacillus plantarum HY7717 improved immunosuppression in cyclophosphamide-treated mice Running Title (within 10 words)Combined immunostimulatory effects of HY8002 and HY7717

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…It was observed that the sow microbiota in the SDP group had a significantly higher relative abundance of the family Lactobacillaceae and genus Lactobacillus . They are bacteria well known for the production of lactic acid during carbohydrate fermentation [ 31 - 33 ]. Previous studies have confirmed that Lactobacillus species have specific probiotic traits which act against pathogenic microorganisms such as E. coli in the intestine [ 34 - 36 ] .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the sow microbiota in the SDP group had a significantly higher relative abundance of the family Lactobacillaceae and genus Lactobacillus . They are bacteria well known for the production of lactic acid during carbohydrate fermentation [ 31 - 33 ]. Previous studies have confirmed that Lactobacillus species have specific probiotic traits which act against pathogenic microorganisms such as E. coli in the intestine [ 34 - 36 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium plays a significant role in the fermentation of dietary fibers and carbohydrates, resulting in the production of short-chain fatty acids (SCFAs), such as acetate, propionate, and butyrate. These SCFAs offer various health benefits, including serving as an energy source for colonocytes, promoting gastrointestinal health, and exhibiting anti-inflammatory properties (Kim et al, 2022). Bifidobacterium, as a type of lactic acid bacteria, generates lactic acid as a metabolic byproduct, which contributes to the maintenance of an acidic gut environment, thereby restraining the proliferation of pathogenic microorganisms (de Souza Oliveira et al, 2012;Pokusaeva et al, 2011).…”
Section: Fimm Incubation Can Imply Changes In Intestinal Robustnessmentioning
confidence: 99%
“…이들은 상피세포에 부착하고 병원체의 부착능력을 물리적으로 차단함으 로써 병원체의 정착을 억제한다 [3]. 또한 장 내에서 여러 가지 대사산물을 생성하여 영양소를 제공하 고, 장 내 면역 반응을 조절하고 면역 세포의 활동을 촉진시켜 면역 관련 질환의 예방 및 완화에 기여할 수 있다 [4][5][6]. 프로바이오틱스는 장내에서 염증성 사이토카인의 수준을 조절하여 염증을 억제 하는 효과도 있다.…”
Section: ) 프로바이오틱스의 효과unclassified